Preparation of oxidation protective MoSi2–SiC coating on graphite using recycled waste MoSi2 by one-step spark plasma sintering method. Issue 17 (1st December 2019) - Chen, Peng; Zhu, Lu; Ren, Xuanru; Kang, Xueqin; Wang, Xiaohong; Feng, Peizhong
Abstract: In order to prepare MoSi2 –SiC coating rapidly and controllably on the basis of recycling of Mo resources, waste MoSi2 heating element rods were used as raw materials to fabricate MoSi2 –SiC coating on graphite substrate by SPS method through one step. Microstructural evolution and phase transformation of the coating before and after oxidation were characterized and the oxidation behaviors of deposited coating were studied in air at 1400 °C and 1200 °C. The results showed that the coating was mainly composed of MoSi2, SiC and Si, which means that the SiC phase was synthesized in a short-time sintering process. The prepared coating was about 600 μm in thickness, presenting a dense structure without any cracks. The adhesive strength of prepared coating was tested by scratch test and the adhesive strength of MoSi2 –SiC coating is about 41.25 N. After high temperature oxidation, the coating surface was covered by a dense and smooth SiO2 film. The protective SiO2 film could prevent the diffusion of oxygen during oxidation. As a result, the mass change of oxidation sample followed a parabolic law and the final mass gain was 9.932 mg/cm 2 after 90 h oxidation at 1400 °C.